PENGARUH KOMPETENSI, INDEPENDENSI, DAN OBJEKTIVITAS TERHADAP KUALITAS AUDIT (Studi Kasus Pada Kantor Akuntan Publik di Kota Semarang) - Fajar Lia Agustina, 15.05.52.0034; Srimindarti, Ceacilia (Students' Journal of Accounting and Banking, 2019)
This study aimed to examine audit quality. The population in this study are all auditors who work in Public Accounting Firm in Semarang. Sampling method used convenience sampling method and obtained a sample of 95 respondents. The method of collecting primary data was conducted through survey method by questionnaire. The data obtained were analyzed using multiple linear regression model.The results of this study show that competence have not affect on audit quality, independence have not affect on audit quality, and objectivity has effect on audit quality.